PENGGUNAAN FOAM BITUMEN UNTUK DAUR ULANG PERKERASAN JALAN - R. Anwar Yamin; Djoko Widayat (Direktorat Bina Teknik Jalan dan Jembatan, 2008)
Restoration of pavement failure was usually done by repairing the damaged segments, by improving pavement structural capacity, by overlaid or by demolished the existing asphalted layer followed by repairing and adding a base layer and followed by overlaid a new asphaltic layer as its surfacing. All of those activities needs fresh materials and can change pavement elevation. Repairing and improving structural capacity of pavement by reused (recycling) the existing pavement materials may be a solution that could be done. A number of materials type can be used either for repairing or for improving the quality of recycling materials, one of them are foam bitumen. Foam bitumen is a mixture of bitumen, water and air in a certain proportion. Foam bitumen produced by injecting water into hot bitumen in the foaming chamber. Foam bitumen can be used as a stabilizer for all type of materials including recycling pavement materials. The use of foam bitumen should be combined with the active filler (cement or lime) in the recycling pavement materials. There were many factors affect the successful in making the recycling by used of foam bitumen. This paper tried to give a description of foam bitumen characteristics, factors affecting in making foam bitumen, the type of materials that can be recycled by foam bitumen, the laboratory and field performance of recycled pavement materials. Key Words: Foam bitumen, stabilizer recycling laboratory and field performance